2017
DOI: 10.1007/s00198-017-4317-4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life for up to 18 months after low-energy hip, vertebral, and distal forearm fractures—results from the ICUROS

Abstract: Hip, vertebral, and distal forearm fractures incur substantial loss in QoL and for patients with hip or vertebral fracture, QoL is markedly impaired for at least 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 28 publications
2
71
1
3
Order By: Relevance
“…QALYs lost due to fragility fractures were estimated from fracture-based HRQoL, fracture risks and death rates [40][41][42]. Methods are summarised in the Appendix (8: Qualityadjusted life years).…”
Section: Quality-adjusted Life Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…QALYs lost due to fragility fractures were estimated from fracture-based HRQoL, fracture risks and death rates [40][41][42]. Methods are summarised in the Appendix (8: Qualityadjusted life years).…”
Section: Quality-adjusted Life Yearsmentioning
confidence: 99%
“…To measure this loss of productivity, data collected in the International Costs and Utilities Related to Osteoporotic Fractures Study (ICUROS) [41,45,46] were used to estimate the number of sick days taken by nonretired individuals from the ages of 50 to 65 years in the year following an osteoporotic fracture. Since Germany was not included in the 11 countries that made up the ICUROS study, a combination of the other 5 countries, as well as Austria and Estonia, termed ICUROS Europe, was used as a substitute measure for the EU6.…”
Section: Loss Of Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these issues and to estimate the costs and quality of life related to fractures in a number of countries across the world, the International Osteoporosis Foundation initiated the International Costs and Utilities Related to Osteoporotic Fractures Study (ICUROS) in 2007. Results of the ICUROS [8,9] showed that fragility hip, vertebral, and distal forearm fractures resulted in substantial QoL loss directly after fracture. While QoL improved with time, 18 months after fracture, mean health state utility values (HSUVs) were lower than before the fracture in patients with hip fracture (0.66 vs. 0.77 p < 0.001) and vertebral fracture (0.70 vs.0.83 p < 0.001) [8].…”
Section: Introductionmentioning
confidence: 99%
“…(3)(4)(5) An accurate assessment of HRQL is essential for both economic modeling and policy making. Although many studies have examined HRQL of individuals with osteoporosis and fractures, aiming to determine the utility weights associated with different types of fractures (6)(7)(8)(9)(10)(11) or the association between utility loss, prior fracture, and hospitalization across different countries, (12) little research has explored the impact of single and multiple fragility fractures over a prolonged period of time (10 years or more). A study that examined utility loss over the longest time frame was published by Papaioannou and colleagues.…”
Section: Introductionmentioning
confidence: 99%